Autoantibody targets in vaccine-associated narcolepsy. (17th August 2016) - Häggmark-Månberg, Anna; Zandian, Arash; Forsström, Björn; Khademi, Mohsen; Lima Bomfim, Izaura; Hellström, Cecilia; Arnheim-Dahlström, Lisen; Hallböök, Tove; Darin, Niklas; Lundberg, Ingrid E.; Uhlén, Mathias; Partinen, Markku; et al.
Abstract: Narcolepsy is a chronic sleep disorder with a yet unknown cause, but the specific loss of hypocretin-producing neurons together with a strong human leukocyte antigen (HLA) association has led to the hypothesis that autoimmune mechanisms might be involved. Here, we describe an extensive effort to profile autoimmunity repertoires in serum with the aim to find disease-related autoantigens. Initially, 57 serum samples from vaccine-associated and sporadic narcolepsy patients and controls were screened for IgG reactivity towards 10 846 fragments of human proteins using planar microarrays. The discovered differential reactivities were verified on suspension bead arrays in the same sample collection followed by further investigation of 14 antigens in 176 independent samples, including 57 narcolepsy patients. Among these 14 antigens, methyltransferase-like 22 (METTL22) and 5'-nucleotidase cytosolic IA (NT5C1A) were recognized at a higher frequency in narcolepsy patients of both sample sets. Upon sequence analysis of the 14 proteins, polymerase family, member 3 (PARP3), acyl-CoA-binding domain containing 7 (ARID4B), glutaminase 2 (GLS2) and cyclin-dependent kinase-like 1 (CDKL1) were found to contain amino acid sequences with homology to proteins found in the H1N1 vaccine. These findings could become useful elements of further clinical assays that aim towards a better phenotypic understanding of narcolepsy and its triggers.